Isolation and Characterization of Agarolytic Microorganisms and Purification of an Extracellular Enzyme Agarase - Thulasidas, Srinivasan (International Journal of Pharmaceutical & Biological Archive, 2012)
Isolation and Characterization of Agarolytic Microorganisms and Purification of an Extracellular Enzyme Agarase